Effect of Workpiece Volume on Shell Wall Thickness Reduction in Rapid Casting of Aluminum using Three-Dimensional Printing - Singh, Rupinder; Singh, Rajinder (Universiti Malaysia Pahang, 2012)
The purpose of the present work is to study the effect of workpiece volume on reducing the shell wall thickness in rapid shell casting based upon three-dimensional printing (3DP) technology, and to evaluate the dimensional accuracy and mechanical properties of aluminum (Al) castings obtained as per the ISO standard UNIEN 20286-I (1995). Starting from the identification of component/benchmark, castings of different volumes (corresponding to workpieces of ɸ60 mm, ɸ50 mm and ɸ40 mm) were produced with different shell wall thicknesses. Measurements on a coordinate measuring machine (CMM) allowed the calculation of the dimensional tolerances of the castings produced. Some important mechanical properties were also compared to verify the suitability of the castings. The research proved that having a shell wall thickness with a value less than that recommended (12 mm) is more suitable from a dimensional accuracy and economic point of view (irrespective of the workpiece volume within the given selected range). All the castings produced with different shell thicknesses are acceptable as per the ISO standard. The results of the study suggest that workpiece volume has an unnoticeable effect on reducing the shell wall thickness for the selected range of volumes of casting. Furthermore, the hardness of castings produced is almost same for all shell wall thicknesses, from 12 mm to 1 mm. The results are supported by cooling (time-temperature) curves, which show unnoticeable changes in the rate of heat transfer at different shell wall thicknesses. Keeping in mind the cost effectiveness of the process, one (1) mm shell wall thickness has been recommended for the production of castings. For a 1 mm shell wall thickness, the production cost and time are reduced by 67.38% and 44.87% (for ɸ60 mm workpieces), 64.51% and 44.62% (for ɸ50 mm workpieces), and 69.50% and 59.64% (for ɸ40 mm workpieces), respectively.